2012
DOI: 10.1021/jf3020574
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Liquid Chromatography–Mass Spectrometry Profiling of Phenolic Compounds for Evaluation of Olive Oil Bitterness and Pungency

Abstract: Bitterness and pungency are important parameters for olive oil quality. Therefore, two instrumental methods for evaluation of these taste attributes were developed. The first one is based on the photometric measurement of total phenolic compounds content, whereas the second one is based on the semiquantitative evaluation of hydrophilic compounds by highperformance liquid chromatography−mass spectrometry (HPLC-MS). Evaluation of total phenolic compounds content was performed by a modified method for the determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 24 publications
1
39
0
1
Order By: Relevance
“…During mechanical pressing, hydrolysis reactions of the secoiridoids lead to the formation of the respective aglycons [4]. Oleuropein aglycon and ligstroside aglycone are present in EVOOs in the form of various isomers [2,14,15]; flavonoids are represented by apigenin (AP) and luteolin (LU), and, finally, lignans include pinoresinol and acetoxypinoresinol [4].…”
Section: Introductionmentioning
confidence: 99%
“…During mechanical pressing, hydrolysis reactions of the secoiridoids lead to the formation of the respective aglycons [4]. Oleuropein aglycon and ligstroside aglycone are present in EVOOs in the form of various isomers [2,14,15]; flavonoids are represented by apigenin (AP) and luteolin (LU), and, finally, lignans include pinoresinol and acetoxypinoresinol [4].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids (C 6 C 3 C 6 ) frequently found in olives include luteolin-7-glucoside, cyanidin-3glucoside, cyanidin-3-rutinoside, rutin, apigenin-7-glucoside, quercetin-3-rhamnoside, and luteolin. Secoiridoids are phenolic compounds found in very few edible plants apart from olives and are among the more important compounds in regard to sensory perception of bitterness [2,26]. Secoiridoids are characterized by an exocyclic 8,9-ole nic functionality, comprised of an elenolic acid and a glucosidic residue, also known as an oleosidic skeleton.…”
Section: Phenolic Compounds In Olivesmentioning
confidence: 99%
“…Sensory studies that examine bitterness in olive products have been conducted using either taste dilution analysis (TDA) or correlating bitterness of olive oil with semiquantitative concentration of measured phenolics [26,32,34]. TDA of oleuropein and oleuropein aglycone indicated that these compounds are bitter at a concentration of 50 µg per 1 cm paper square [32].…”
Section: Sensory Studies In Bitternessmentioning
confidence: 99%
“…Many analytical methods have been developed for the determination of OE in various matrices such as olive oil (Dierkes et al , ), table olives (Zoidou et al , ), byproducts of the olive oil industry (Lozano‐Sánchez et al , ) and biological fluids (Bazoti et al , ). Thus, OE has been analysed by employing high‐performance liquid chromatography coupled with ultraviolet detection (HPLC‐UV) (Ortega‐García & Peragón, ), HPLC‐fluorescence (Tan et al , ) and HPLC coupled with tandem mass spectrometry (HPLC‐MS/MS) (Zhou et al , ).…”
Section: Introductionmentioning
confidence: 99%